Comparative Analysis Of Economic Growth In Jakarta And East Kalimantan 2018-2022 - Angraini, Liana; Moehadi, Moehadi; Susilo, Joko Hadi (MediaTrend, 2024)
This research aims to determine the effect of unemployment and poverty on economic growth in Jakarta and East Kalimantan. This research also compares the effect of un- employment and poverty on economic growth between Jakarta and East Kalimantan. This type of research approach is carried out using a descriptive quantitative analysis approach. The results of this research found that in Jakarta unemployment and poverty both had a significant negative effect on economic growth, while in East Kalimantan it showed that unemployment had a significant negative effect on economic growth and poverty had an insignificant effect on economic growth. So this research recomandends that East Kalimantan as a candidate for the new capital city must pay attention to the unemployment rate to increase economic growth, while in Jakarta it must pay attention to two aspects of the importance of unemployment and poverty. This research provides new insights into comparative economic growth in Jakarta and East Kalimantan.